Risk Assessment of E. coli Survival Up to the Grazing Exclusion Period After Dairy Slurry, Cattle Dung, and Biosolids Application to Grassland - Ashekuzzaman, S. M.; Richards, Karl; Ellis, Stephanie; Tyrrel, Sean; O'Leary, Emma; Griffiths, Bryan; Ritz, Karl; Fenton, Owen (Frontiers in Sustainable Food Systems, 2018)
Grassland application of dairy slurry, cattle dung, and biosolids offers an opportunity to recycle valuable nutrients (N, P, and K), which may all introduce pathogens to the soil environment. Herein, a temporal risk assessment of the survival of Escherichia coli (E. coli) up to 40 days in line with the legislated grazing exclusion time points after application was examined across six scenarios: (1) soil and biosolids mixture, (2) biosolids amended soil, (3) dairy slurry application, (4) cattle dung on pasture, (5) comparison of scenario 2, 3, and 4, and (6) maximum legal vs. excess rate of application for scenario 2 and 3. The risk model input parameters were taken or derived from regressions within the literature and an uncertainty analysis (n = 1,000 trials for each scenario) was conducted. Scenario 1 results showed that E. coli survival was higher in the soil/biosolids mixture for higher biosolids portion, resulting in the highest 20 day value of residual E. coli concentration (i.e., C20, log10 CFU g−1 dw) of 1.0 in 100% biosolids or inoculated soil and the lowest C20 of 0.098 in 75/25 soil/biosolids ratio, respectively, in comparison to an average initial value of ~6.4 log10 CFU g−1 dw. The E. coli survival across scenario 2, 3, and 4 showed that the C20 value of biosolids (0.57 log10 CFU g−1 dw) and dairy slurry (0.74 log10 CFU ml−1) was 2.9–3.7 times smaller than that of cattle dung (2.12 log10 CFU g−1 dw). The C20 values of biosolids and dairy slurry associated with legal and excess application rates ranged from 1.14 to 1.71 log10 CFU ha−1, which is a significant reduction from the initial concentration range (12.99 to 14.83 log10 CFU ha−1). The E. coli survival in un-amended soil was linear with a very low decay rate resulting in a higher C20 value than that of biosolids or dairy slurry. The risk assessment and uncertainly analysis showed that the residual concentrations in biosolids/dairy slurry applied soil after 20 days would be 45–57% lower than that of the background soil E. coli concentration. This means the current practice of grazing exclusion times is safe to reduce the risk of E. coli transmission into the soil environment.